Self-Regulation Guide for the Development of Argumentation Skills in Nursing Care Management: A Mixed Study; [Guía de Autorregulación Para el Desarrollo de Habilidades de Argumentación en la Gestión del Cuidado de Enfermería: Un Estudio Mixto] - Contreras-Flores, V (Elsevier Espana S.L.U, 2024)
Introduction: Self-regulation of learning and argumentative skills are fundamental competencies for the formation of undergraduate Nursing students, allowing them to manage safe and quality care, favoring the satisfaction of society s demands. Due to this, during the year 2021, in Nursing students of the University of Santiago de Chile who took the subject Management of adult and elderly care I, belonging to the 5th semester, a methodological innovation was carried out by incorporating to their teaching-learning process a semester self-regulation guide, focused on strengthening the argumentation regarding the meta-concept of care management, which was designed respecting the theoretical phases of the process of self-regulation of learning: planning, execution and self-reflection. The objective of the study was to investigate the students perceptions and their level of satisfaction with respect to the strengthening of the argumentation, and the facilitation of their learning through the development of the guide. Methods: The study was conceived under the interpretive paradigm, justifying a mixed design, descriptive in scope, with a phenomenological approach and using a concurrent embedded design of dominant model, being the qualitative approach predominant. Results: The participants descriptions of the phenomenon studied were interpreted, highlighting that they perceived the development of the self-regulation guide as favorable for strengthening their argumentative skills and facilitating their learning, while at the same time they valued this experience with a high level of satisfaction. Conclusions: Students perceived the self-regulation guide as a contribution to their professional training. © 2024 The Authors